2020
DOI: 10.1002/hpja.320
|View full text |Cite
|
Sign up to set email alerts
|

Changing health workforce attitudes to promote improved physical health in mental health service users: Keeping our Staff in Mind (KoSiM)

Abstract: Human Rights: All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki Declaration and its later amendments or comparable ethical standards. Ethical approval: The study protocol was approved by the South Eastern Sydney Local Health District Human Research Ethics Committee (HREC 15/054).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 29 publications
5
37
0
Order By: Relevance
“…It may, therefore, be that an intervention to increase PA and reduce SB among mental health professionals would have indirect positive effects on their PA and SB counselling practices. The results of our study are in accordance with the recent findings of Rosenbaum et al [47] who found improvements in perceived barriers, attitudes, knowledge and confidence in promoting physical health in clients following a lifestyle intervention among clinical and non-clinical mental health staff working in mental health services in Australia.…”
Section: Plos Onesupporting
confidence: 92%
“…It may, therefore, be that an intervention to increase PA and reduce SB among mental health professionals would have indirect positive effects on their PA and SB counselling practices. The results of our study are in accordance with the recent findings of Rosenbaum et al [47] who found improvements in perceived barriers, attitudes, knowledge and confidence in promoting physical health in clients following a lifestyle intervention among clinical and non-clinical mental health staff working in mental health services in Australia.…”
Section: Plos Onesupporting
confidence: 92%
“…As previously noted, overall outcomes of the KoSiM intervention have been previously reported, 27 and this report focuses on the exercise component of the intervention.…”
Section: Methodsmentioning
confidence: 77%
“…An overall description of the KoSiM intervention and outcomes has been published. 27 This report focuses on the impact on exercise and fitness outcomes for wave 2 of KoSiM. Only fitness data from wave 2 were analysed due to limited data collection of fitness measures during wave 1.…”
Section: Introductionmentioning
confidence: 99%
“…A description of the entire KoSiM program is described elsewhere. 17 Briefly, the structured, multidisciplinary program consisted of an initial assessment by a mental health Clinical Nurse Consultant (CNC), a dietitian and an exercise physiologist.…”
Section: Me Thodsmentioning
confidence: 99%